PELATIHAN PENYUSUNAN LAPORAN KEUANGAN YAYASAN PUTRA MANDIRI SUMATRA SELATAN - Fitria Marsiya; Marsinah; Hatidah; RA Rodia Fitri Indriani (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Training in preparing financial reports for financial managers of the Putra Mandiri foundation is to improve skills and broaden horizons in the preparation of financial reports for non-profit organizations. This service activity was held on Tuesday, 20 October 2022 at SMK Putra Mandiri which was attended by 19 participants. The training activities went smoothly as scheduled. The participants were enthusiastic in following the material. The method used in this activity is the method of lecturing, question and answer, and discussion. The result of this training shows that the participants feel the importance of this training because by preparing financial reports based on standards, it will increase accountability and transparency.